Molecular and Cytogenetic Characterization of Six Wheat-Aegilops markgrafii Disomic Addition Lines and Their Resistance to Rusts and Powdery Mildew - Niu, Zhixia; Chao, Shiaoman; Cai, Xiwen; Whetten, Rebecca B.; Breiland, Matthew; Cowger, Christina; Chen, Xianming; Friebe, Bernd; Gill, Bikram S.; Rasmussen, Jack B.; Klindworth, Daryl L.; Xu, Steven S. (Frontiers in Plant Science, 2018)
Aegilops markgrafii (Greuter) Hammer is an important source of genes for resistance to abiotic stresses and diseases in wheat (Triticum aestivum L.). A series of six wheat ‘Alcedo’-Ae. markgrafii chromosome disomic addition lines, designated as AI(B), AII(C), AIII(D), AV(E), AIV(F) and AVIII(G) carrying the Ae. markgrafii chromosomes B, C, D, E, F and G, respectively, were tested with SSR markers to establish homoeologous relationships to wheat and identify markers useful in chromosome engineering. The addition lines were evaluated for resistance to rust and powdery mildew diseases. The parents Alcedo and Ae. markgrafii accession ‘S740-69’ were tested with 1500 SSR primer pairs and 935 polymorphic primers were identified. After selecting for robust primers and confirming the polymorphisms on the addition lines, 132 primers were considered useful for engineering and establishing homoeologous relationships. Based on the marker analysis, we concluded that the chromosomes B, C, D, E, F, and G belong to wheat homoeologous groups 2, 5, 6, 7, 3, and 4, respectively. Also, we observed chromosomal rearrangements in several addition lines. When tested with 20 isolates of powdery mildew pathogen (Blumeria graminis f. sp. tritici) from five geographic regions of the U.S., four addition lines (AIII(D), AV(E), AIV(F), and AVIII(G)) showed resistance to some isolates, with addition line AV(E) being resistant to 19 of 20 isolates. The addition lines were tested with two races (TDBJ and TNBJ) of the leaf rust pathogen (Puccinia triticina), and only addition line AI(B) exhibited resistance at a level comparable to the Ae. markgrafii parent. Addition lines AII(C) and AIII(D) had been previously identified as resistant to the Ug99 race group of the stem rust pathogen (Puccinia graminis f. sp. tritici). The addition lines were also tested for resistance to six U.S. races (PSTv-4, PSTv-14, PSTv-37, PSTv-40, PSTv-51, and PSTv-198) of the stripe rust pathogen (Puccinia striiformis f. sp. tritici); we found no resistance either in Alcedo or any of the addition lines. The homoeologous relationships of the chromosomes in the addition lines, molecular markers located on each chromosome, and disease resistance associated with each chromosome will allow for chromosome engineering of the resistance genes.